Examining the several vegetation indices values to estimate carbon stock at the mining reclamation area of PT. Adaro Indonesia, South Kalimantan - Rachmanadi, Dony; Nugraha, Luthfan Meilana; Choiron, Dodik; Riadhah, Mekka; Husin, Rusdi; Triwibowo, Didik; Ajiddinnor, Ajiddinnor (Journal of Degraded and Mining Lands Management, 2026)
Revegetation of coal mine reclamation areas contributes to environmental improvement by sequestering carbon through vegetation. This study aimed to estimate carbon stocks in reclaimed and post-mining areas of PT Adaro Indonesia using various vegetation indices to assess the areas' contribution to carbon sequestration and identify the most effective estimation method. Six vegetation indices—NDVI, RVI, SAVI, GNDVI, RDVI, and IPVI—were derived from drone-based multispectral imagery and combined with field sampling for enhanced accuracy. Carbon stock was calculated based on biomass, which correlates with tree size and other observable carbon pools. The results showed that, although the Tutupan site had lower vegetation diversity, it stored more carbon than the Paringin site. Among the indices tested, NDVI produced the most robust estimation model, demonstrating a high correlation and low standard error, indicating its strong predictive model for assessing carbon stocks in reclaimed mining lands.